Above Room‐Temperature Reversible Phase Transition and Nonlinear Optical Material PO(CH2CH2CH2CF3)3 with Hirshfeld Surface Analyses - Yu, Yanhong; Hu, Zhongyu; Xiong, Zhenhua (Zeitschrift für anorganische und allgemeine Chemie (1950), 2025)
The multifunctional materials with dielectric and nonlinear optical properties have attracted the attention of many scientists with potential applications in data communication, photoelectric devices, information processing, etc. Herein, one compound PO(CH2CH2CH2CF3)3 1, which underwent an obvious reversible structural phase transition, is reported. In the single‐crystal structure data, it is shown that space group of 1 changes from R3c to R3m, from one polar space group to another polar space group, and the dielectric constant has frequency dependence. The second harmonic generation (SHG) value is 0.50 at room‐temperature phase. The SHG value changes abruptly at around 349 K. The SHG value is about 1.09 at high‐temperature phase. Hirshfeld surface analyses reveal that H···F/F···H interactions make major contribution to the total forces, and the forces of the two kinds of hydrogen bonds are different at different phases. In the Hirshfeld surface analyses, difference in hydrogen bond interactions of organic compound PO(CH2CH2CH2CF3)3 at different dielectric and nonlinear optical states is shown.